PELATIHAN PENULISAN KARYA ILMIAH BAGI GURU SEKOLAH DASAR - Ismu Sukamto; Siska Mega Diana; Dayu Rika Perdana; Amrina Izzatika (Ruang Pengabdian : Jurnal Pengabdian Kepada Masyarakat, 2022)
The profession as a teacher is required to have the ability to write scientific papers. This is stated in the Regulation of the Minister for Empowerment of State Apparatus and Bureaucratic Reform No. 16 of 2009 concerning Teacher's Functional Positions and Credit Scores. In addition, writing scientific papers can be a medium for sharing knowledge related to educational innovation. Therefore, the purpose of this activity is to increase the interest, knowledge, and skills of teachers in writing scientific papers. This community service activity was carried out with a target of 20 elementary school teachers in Metro City. This training activity has 2 stages, the presentation of material about writing scientific papers and the practice of writing scientific papers. Based on the data from the implementation, the training went well. However, there are obstacles to its implementation, namely: at the pretest and post-test stages in the form of an internet connection. In addition, this training was quite effective in increasing participants' knowledge of scientific writing with an n-gain of 0.303. The results of this activity become a reference for policymakers to organize teacher improvement programs in scientific writing and publications. Keywords:elementary school teachers; scientific papers; trainingAbstrakBerprofesi sebagai seorang guru dituntut untuk memiliki kemampuan menulis karya tulis ilmiah. Hal ini tercantum dalam Peraturan Menteri Pendayagunaan Aparatur Negara dan Reformasi Birokrasi No. 16 Tahun 2009 tentang Jabatan Fungsional Guru dan Angka Kreditnya. Selain itu, menulis karya tulis ilmiah dapat menjadi media berbagi ilmu terkait inovasi pendidikan. Oleh karena itu, tujuan dari pelaksanaan kegiatan ini adalah untuk meningkatkan minat, pengetahuan dan keterampilan guru dalam penulisan karya ilmiah. Kegiatan pengabdian masyarakat ini dilakukan di Kota Metro dengan sasaran 20 guru SD yang ada di Kota Metro. Kegiatan pelatihan ini memiliki 2 tahapan, pemaparan materi tentang penulisan karya ilmiah dan praktik penulisan karya tulis ilmiah. Berdasarkan data hasil pelaksanaan, pelatihan berjalan dengan baik. Meskipun demikian, terdapat kendala dalam pelaksanaannya, yaitu: pada tahap pretest dan posttest berupa koneksi internet. Selain itu, pelatihan ini cukup efektif dalam meningkatkan pengetahuan peserta tentang karya tulis ilmiah dengan n-gain sebesar 0,303. Hasil dari kegiatan ini menjadi rujukan bagi pemegang kebijakan untuk menyelenggarakan program peningkatan guru dalam penulisan karya tulis ilmiah dan publikasi.DOI: https://doi.org/10.23960/rp/v2i1.hal.81-86